Influence of fabric architecture on energy absorption efficiency of soft armour panel under ballistic impact. (15th September 2019) - Yang, Yanfei; Chen, Xiaogang
Abstract: This study aims to optimize fabric architecture of soft armour panel in order to improve ballistic performance without increasing weight. Finite Element (FE) analysis, in conjunction of ballistic test, was used to investigate ballistic responses of fabrics with different weave parameters under ballistic impact. In an individual layer, the yarn crimp effect on energy absorption exhibits significant in the consideration of yarn count, weave density and areal density of fabric. FE results indicate that the stress on the high crimp fabric fluctuated more severely at the crossover and fail earlier than that of the fabric with low crimp. In a multi-layer panel, the yarn crimp is still influential on energy absorption of each fabric layer, Backface Signature (BFS) and perforation ratio of the whole panel. The panel combining low crimp fabrics shows that the energy absorption efficiency of each layer is higher than that of the panel composed of high crimp fabrics. However, the panel with low crimp fabrics possesses enlarged BFS and increased perforation ratio. These findings are greatly meaningful for the design of soft armour panel.